Enhanced Reproductive Thermotolerance of the Tomato high pigment 2 Mutant Is Associated With Increased Accumulation of Flavonols in Pollen - Rutley, Nicholas; Miller, Golan; Wang, Fengde; Harper, Jeffrey F; Miller, Gad; Lieberman-Lazarovich, Michal (Frontiers in Plant Science, 2021)
Climate change has created an environment where heat stress conditions are becoming more frequent as temperatures continue to raise in crop production areas around the world. This situation leads to decreased crop production due to plant sensitivity to heat stress. Reproductive success is critically dependent on plants’ ability to produce functional pollen grains, which are the most thermo-sensitive tissue. Flavonols are plant secondary metabolites known for their potent antioxidative activity, essential for male fertility in several species including tomato, and implicated in heat stress tolerance. Since flavonols are highly abundant in fruits of the tomato high pigment 2 (hp2) mutant, we tested the level of flavonols in pollen of this mutant, under the hypothesis that increased accumulation of flavonols would render pollen more tolerant to heat stress. Indeed, pollen from two alleles of the hp2 mutant was found to have flavonols levels increased by 18 and 280% compared with wild-type (WT) under moderate chronic heat stress (MCHS) conditions. This mutant produced on average 7.8-fold higher levels of viable pollen and displayed better germination competence under heat stress conditions. The percentage of fully seeded fruits and the number of seeds per fruit were maintained in the mutant under heat stress conditions while decreased in wild-type plants. Our results strongly suggest that increased concentrations of pollen flavonols enhance pollen thermotolerance and reproductive success under heat stress conditions. Thus, the high flavonols trait may help frame the model for improving crop resilience to heat stress.